2019
DOI: 10.1111/ajgw.12415
|View full text |Cite
|
Sign up to set email alerts
|

Scion–rootstock interactions influence the growth and behaviour of the grapevine root system in a heavy clay soil

Abstract: Background and Aims: Generally, grapevine roots have been less studied than the above-ground parts of the plant. Here we analyse scion-rootstock interactions in mature vines growing in a heavy clay soil in a climate characterised by severe summer drought to investigate the effect of the scion-rootstock interaction in a suboptimal soil. Methods and Results: The rootstocks, 34 Ecole de Montpellier, 140 Ruggeri and 1103 Paulsen, were grafted onto Nerello Mascalese and Nero d'Avola scions and assessed along with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…The scion genotype affected tip density particularly when the rootstock was PN; tip density was higher in 1103P/PN compared to PN/PN; this could suggest that the scion can exert long-distance regulation of root branching in grapevine. This hypothesis is supported by a study on the effect of the scion on the root system of mature plants in a 17 year-old vineyard, which showed that the scion could affect root biomass, shoot:root ratio, root density (per m² of soil) and root distribution in the soil (Ferlito et al, 2020).…”
Section: Growth Of Young Grapevines Is Scion Dependant Under Non-limiting Phosphate Conditionsmentioning
confidence: 80%
“…The scion genotype affected tip density particularly when the rootstock was PN; tip density was higher in 1103P/PN compared to PN/PN; this could suggest that the scion can exert long-distance regulation of root branching in grapevine. This hypothesis is supported by a study on the effect of the scion on the root system of mature plants in a 17 year-old vineyard, which showed that the scion could affect root biomass, shoot:root ratio, root density (per m² of soil) and root distribution in the soil (Ferlito et al, 2020).…”
Section: Growth Of Young Grapevines Is Scion Dependant Under Non-limiting Phosphate Conditionsmentioning
confidence: 80%
“…Less research has been conducted on the effects of the scion on the rootstock, and, to date, this effect has been examined only on physical rootstock properties such as root biomass and length [28]. The interaction between rootstocks and scions also remains understudied, but research has shown that it can affect yield and quality of grapes [29], and root behavior and plant growth [30]. With grafting, scions and rootstocks each maintain their own genetic identity [24], and in other plant species this has led to changes in bacterial diversity [31] or community structure [32].…”
Section: Introductionmentioning
confidence: 99%
“…A fundamental question in plant biology is how root systems influence phenomic variation in above-ground shoot systems including leaves, flowers, and fruits. Grafting, a common horticultural manipulation that joins the shoot system of one individual (the scion) with the root system of another individual (the rootstock), is commonly used in crop species to confer favorable phenotypes to commercial scions [ 6 ], including enhanced disease resistance [ 7 , 8 ], fruit quality, plant form [ 9 ], response to water stress [ 10 ], and growth on particular soils [ 11 , 12 ]. Because grafting often uses clonally propagated materials, it is possible to manipulate and replicate different combinations of root systems and shoot systems, offering a valuable experimental system in which root system effects on shoot system phenotypes can be evaluated.…”
Section: Introductionmentioning
confidence: 99%